Combination of pembrolizumab and axitinib: a new gold standard in the first-line therapy for metastatic clear-cell renal-cell carcinoma? - R. A. Gafanov (Onkourologiâ, 2020)
The treatment strategy for metastatic renal cell carcinoma (mRCC) has evolved with the emergence of anti-angiogenic drugs, in particular tyrosine kinase inhibitors (TKIs) targeting the vascular endothelial growth factor receptor (VEGFR) and immune checkpoint inhibitors (ICIs). Both treatment options improved patient outcomes and altered the natural history of mRCC. Clinical studies have focused on evaluating combination regimens containing ICI and VEGFR-targeted TKIs. The combination of axitinib with pembrolizumab (KEYNOTE-426) showed better results compared to sunitinib in patients with mRCC who had not previously received systemic therapy. In this article, we discuss the rationale for the combination of ICI and TKI based on preclinical data, as well as the clinical results obtained with the combination of axitinib with pembrolizumab in first-line patients in clinical trials.